Trabajo colaborativo y su incidencia en el aprendizaje activo en los estudiantes de quinto año de educación básica de la unidad educativa Francisco Huerta Rendón de la ciudad de Babahoyo provincia los ríos durante el periodo 2017 - Junco Salazar, Carmen Rosa (2017)
This research was carried out in the Educational Unit "Francisco Huerta Rendón Babahoyo province Los Rios, in this prestigious institution has been able to verify the little importance given to this technique of collaborative work which is very important in daily life so that the teacher can implement in an adequate way his teaching in the students which has as purpose to achieve the implementation of certain study techniques. And its benefits that collaborative work offers in the active learning of the students, having as objective to identify the collaborative work in the active learning of the fifth year students of Basic Education, in this study the modality of field, bibliographical, the population that is made up of a determined sample of 60 students. Where the following results were obtained, it could be verified that a large part of teachers do not apply this study technique in the classroom and that many more tools should be implemented in the traditional teaching process to share knowledge, thus building learning through the collaboration of collaborative groups, which aims to innovate new knowledge. The results of this research is to focus an equation program where you can comfort the problems that exist in the classroom when working in groups or work teams with students so that you can achieve active learning of good quality with students and with the due training to the teachers on techniques of collaborative work to improve the active learning in the students, it will be possible to have a better control in the learning and it will be possible to cover those shortcomings that exist in the student who does not learn in a fast way and He is continually distracted.